Determination of pKa values of fluorocompounds in water using 19F NMR. (14th February 2019) - Parman, Elisabeth; Toom, Lauri; Selberg, Sigrid; Leito, Ivo
Abstract: Brønsted acidities of 19 fluorocompounds in the p K a range from 3.5 to 10 have been measured in aqueous solution using an approach involving absolute and relative p K a measurements with 19 F NMR. 19 F NMR has not been frequently used for determining p K a values, but it has a number of advantages, especially when relative values are considered: accurate concentrations not needed, tolerant to impurities, several compounds can be measured simultaneously, several uncertainty sources cancel out. Abstract : Two p K a measurement methods based on 19 F NMR are proposed. Their advantages are compared, and p K a values of 19 fluorocompounds ranging from 3.5 to 10 are reported.